PENGARUH IKAN GABUS TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM DI PUSKESMAS SUNGAI PIRING TAHUN 2019 - rika aldesta; Rifa Rahmi; Fajar Sari Tanberika (Politeknik Kesehatan Kementerian Kesehatan Banten, 2020)
ABSTRACT Handling of any cause of perineum rupture during childbirth should be done immediately with qualityto minimize the possibility of complications such as bleeding, infection, dyspareunia hematoma, and reduced libido that usually accompanies in the cause of perineum rupture. Snakehead Murrel is believed to accelerate wound healing because of its extract as a substitute for serum albumin which is usually used for surgical wound healing. The purpose of this study was to determine the effect of snakehead murrel on the healing of perineal wounds in postpartum mothers in Public Health Center of Sungai Piring in 2019. This study used by quasi-experimental methods with a non-equivalent control group of 60 postpartum mothers who were divided into two groups namely the experimental group and the control group. The population was the first part of postpartum mothers with second-degree perineal injuries from January to June with a sample of 22 respondents. The sampling technique in this study was purposive sampling. Results:there wasa healing of perineal wounds in all members of the experimental group and there was no healing in all control groups at the time of observation on 8th days. Conclusion: there was a significant effect of consuming Snakehead Murrel on the healing of perineal wounds in postpartum mothers.